A 65nm CMOS carrier-aggregation transceiver for IEEE 802.11 WLAN applications - Yi, Xiang (2020)
This work presents a parallel direct-conversion and double-conversion transceiver to solve the problems of crosstalk and LO pulling in the carrier aggregation scenario. An EVM of -34.9 dB is obtained when the output power of the PA driver is 0.4 dBm. Three aggregated carriers with 80 MHz 256-QAM modulation are demonstrated. To the authors' best knowledge, this work is the first CMOS integrated transceiver for IEEE 802.11 WLAN carrier aggregation application.